Zn(II) and Cd(II)-based complexes for probing the enzymatic hydrolysis of Na4P2O7 by alkaline phosphatase in physiological conditions - Das, Priyadip; Sourish, Bhattacharya; Sandhya, Mishra; Das, Amitava (Chemical Communications, 2011)
Newly synthesized Zn(II) and Cd(II)-based complexes show unique selectivity towards inorganic pyrophosphate (PPi) in 100% aqueous medium at pH = 7.4 and act as a "turn-on" and "turn-off" real-time assay, respectively, for the evaluation of the enzymatic activity of alkaline phosphatase.

ZnII-2,2?:6?,2?-terpyridine-based complex as fluorescent chemosensor for PPi, AMP and ADP - Das, Priyadip; Ghosh, Amrita; Kesharwani, Manoj K.; Ramu, Vadde; Ganguly, Bishwajit; Das, Amitava (Europian Journal of Inorganic Chemistry, 2011)
A new ZnII–2,2′:6′,2″-terpyridine complex, derivatized with a coumarin moiety (L1Zn), acts as a fluorescent chemosensor for different biologically important phosphates like PPi, AMP and ADP in mixed aqueous media. Depending on the proportion of the aqueous fraction present in the solvent mixture, L1Zn shows a preference for different phosphate moieties at physiological pH. In an aqueous acetonitrile (2:3, v/v) medium this reagent shows a preference for AMP as compared to ADP, ATP and PPi. The binding affinities of L1Zn with different phosphate ions and associated shifts in the electronic spectra were rationalized by DFT calculations. Such an example of a receptor that is selective for AMP under physiological conditions is rare in the literature.